THE IMPACT OF DIGITAL TECHNOLOGIES ON THE FORMATION OF COMPETITIVE ADVANTAGES OF HOSPITALITY INDUSTRY ENTERPRISES IN CRISIS CONDITIONS - Pereguda, Yuliya; Kryvoberets, Maryna (Social Development: Economic and Legal Issues, 2026)
Digitalization has had a positive impact on the development of the hospitality industry, contributing to a more effective distribution and distribution of hotel products. In crisis conditions, digital technologies allow hotel operators to ensure the adaptability and flexibility of their operational activities, which are highly sensitive to the decline in economic activity. The article aimed to identify the links between digitalization and the formation of competitive advantages of hospitality industry enterprises in crisis conditions. To assess the links, methods of statistical correlation analysis of the indicators of the development of the hospitality industry in the EU member states in 2023 and indicators of the digitalization of the economy in the EU in 2023 were used. The results demonstrate the direct impact of the ICT sector’s share in the gross value added of the EU economies on the level of hotel occupancy, i.e., on the demand for services in the hospitality industry. The post-crisis period of development of the temporary accommodation sector in the EU is characterized by a gradual recovery and an increase in the importance of digitalization for hospitality enterprises. Until the beginning of 2021, the hospitality industry focused on digitizing information and digitizing individual guest service processes. In the context of the decline in revenue caused by the pandemic, the hospitality business was forced to implement digital technologies for adaptation and flexibility of operations. Before the coronavirus crisis, the level of digitalization capability of the hospitality industry and hotel companies was estimated at 26% in 2020, while after the pandemic, the digital readiness and awareness of enterprises increased to 61% in 2023. Marketing using social media, websites for promoting hotel services, technologies for managing customer relationships, and online advertising of services are identified as some of the most important for forming competitive advantages of hotel enterprises. Ukrainian experience in using digital technologies demonstrates their increasing importance for performing various business functions of enterprises in the field of temporary accommodation in 2024–2025.